Pedagogical Content Knowledge: Validation of Basic Teaching Ability for Mathematics Education Preservice Teacher - Lailin Hijriani; Zulkaidah Nur Ahzan; Meiva Marthaulina Lestari Siahaan (Didaktika: Jurnal Kependidikan, 2025)
Research on Pedagogical Content Knowledge (PCK) of prospective Mathematics Education teachers as an answer to the problems being faced is expected to be one of the evaluation tools for the lecture process in order to improve the quality of graduates and by realizing the importance of good PKP skills, a communicative learning atmosphere will be created and create multi-directional interactions between students and lecturers. The subjects in this study consisted of three prospective teacher students who had participated in Field Experience Practice (PPL) activities. The findings of this qualitative study used a triangulation design based on purposive sampling using several instruments including test questions, interview guidelines, and documents. The results of the study indicate that the Pedagogical Content Knowledge of prospective Mathematics Education teachers is in the insufficient category. If this is allowed to continue, it will impact the mathematics education graduates quality.